DEVELOPMENT OF FINANCIAL LITERACY IN SCHOOLS FOR ECONOMY GROWTH OF UZBEKISTAN (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This thesis examines the necessity of developing financial literacy in school education as a key factor in forming an economically sustainable society.